The Effects of Motivation and Interpersonal Communication on Work Productivity Employees in Polytechnic 'X' Bandung, West Java - Budiawan, Andi; Budi Santoso, Anton; Astuti, Eriana; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The relatively low impulse arising from self-employment of employees to increase productivity, in the sense that they tend to wait for orders from the leadership. Extrinsic motivation is still a poor extension to all employees within the meaning of motivation and did not consider the level of heterogeneity that exists in the employee. This makes the indication of a job that does not reach the target time, the number and quality, or a predetermined quality. Frequent errors in carrying out the work, which shows the low effectiveness of the employee. According to provisional estimates, the author of this was due to employee motivation not growing well; besides, motivating leadership is not right when seen from motivational techniques, as well as internal communication has not worked as expected. It is, if not addressed, will influence / result in employee productivity decline, which may be a result of a delay in the achievement of an organization. Based on this phenomenon, the authors were interested in studying and further research. The method used in this research is a descriptive research method that provides an overview or affirmation of a concept, danmenjawab symptoms, and answers questions regarding the status of the study subjects. Methods This descriptive study is associative, namely a study looking for a relationship between one variable and another variable. This research was conducted at the Polytechnic 'X' Bandung. As for research and observations carried out from June to November 2018. The study population is the entire Employee Polytechnic "X," which amounted Engineering samples used in this study is saturated sampling techniques and data analysis is a technique using multiple linear regression analysis using SPSS version 18.From the whole description in the discussion, it was discovered that employee motivation and Interpersonal Communication Polytechnic 'X' Bandung in outline have been as expected and have been running optimally. Similarly, for a variable number of interpretations, the productivity score is 4.42, which is in the category of Very High. It can be concluded in employee productivity has gone well.Based on regression analysis, it turned out that both the independent variables significantly affect the productivity of pegawi, either partially or simultaneously. Based on the analysis, an appropriate calculation of Pearson correlation coefficient (R) obtained a yield of 0.887, which means that the relationship between motivation and interpersonal communication with employee productivity is very tight and strong. Through R squared (R2) of 0.638, it can be said that the magnitude of the coefficient of determination (KD) amounted to 78.70%, which means that 78.70% of employee productivity is influenced by variables motivation and communication, and the remaining 21.30% is influenced by other factors not examined in this study.